TERAPI GIZI PADA PASIEN GERIATRI DENGAN STROKE ISKEMIK, PENYAKIT GINJAL KRONIS, PNEUMONIA, DAN DIABETES MELITUS - Allysa Allysa; Siti Nur Fatimah (Fakultas Kedokteran Universitas Jenderal Achmad Yani, 2026)
Stroke patients are often at risk of malnutrition and dehydration, conditions that can be exacerbated by comorbidities such as chronic kidney disease (CKD), pneumonia, and type II diabetes mellitus (DM II). Nutritional therapy is essential to improve nutritional status and support clinical and metabolic recovery in these patients. The aim of this article is to report the application and outcomes of nutritional therapy in a 62-year-old female patient with ischemic stroke, CKD, pneumonia, and type II diabetes mellitus. This is a case report of a 62-year-old woman diagnosed with ischemic stroke, pneumonia, CKD, and DM II. The patient presented with loss of consciousness (GCS score E2M2V2), left hemiparesis, and edema in the arms, sacral area, and pretibial region. Nutritional therapy was initiated with an initial caloric intake of 800 kcal, gradually increased to a target of 1800 kcal/day, tailored to the patient’s clinical condition and laboratory findings. The nutritional therapy began with 800 kcal/day and was gradually increased. Although the patient’s serum albumin levels improved from 2.49 g/dL to 2.85 g/dL, her kidney function continued to decline, with increasing levels of blood urea nitrogen, creatinine, C-reactive protein (CRP), and procalcitonin (PCT). The patient ultimately experienced cardiac arrest on the 29th day of treatment, and the family declined resuscitation efforts. Despite the nutritional therapy, the patient’s metabolic abnormalities could not be fully corrected without hemodialysis, which was declined by the family. The therapy provided some support but was insufficient to prevent the progression of renal failure and the patient’s subsequent death. Keywords: chronic kidney disease, nutritional therapy, pneumonia, stroke, type II diabetes mellitus DOI : 10.35990/mk.v9n1.p91-103